Authentic and Heterogeneous Mimesis: Reflection and Self-reflexivity in Todor Pavlov and Yuri Lotman - Spassova, Kamelia (Slavica tergestina, 2018)
The paper focuses on the mirror as a metaphor in the Marxist and structuralist paradigm by means of which contradictory concepts of literature in terms of its mimetic activity crystallize. The term mimetic reflection was in circulation in the Soviet Union at that time as one of the key concepts of the dogmatic Marxist-Leninist aesthetics and especially of Todor Pavlov’s theory of reflection, in which literature is seen as an authentic reflection of reality. A detachment of reflection theory can be traced in the works of Lotman and Kristeva. In their theoretical works the mirror functions as a metaphor for intertextuality, and self-reflexivity as the ability of literature to refer to its own techniques, its own process of creation and its own fictional status. Thus, the article outlines two mimetic types: authentic mimesis, represented by Pavlov’s theory, and on the other side, heterogeneous creative mimesis, developed by Lotman’s text within a text structure and Kristeva’s genotext in merging Jakobson and Bakhtin’s legacy.